2008
DOI: 10.1194/jlr.m700581-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine prevents UV-induced decrease of type I procollagen and increase of MMP-1 in dermal fibroblasts and human skin in vivo

Abstract: In an effort to find topical agents that prevent or retard cutaneous aging, seven functional lipids were screened for their procollagen-upregulating and matrix metalloproteinase (MMP)-1-downregulating activities in human dermal fibroblasts by Western blotting. The preventive effect on ultraviolet (UV)-induced decrease of procollagen was demonstrated in phosphatidylserine (PS), lysophosphatidylserine (LPS), lysophosphatidic acid (LPA), N-acetyl phytosphingosine (NAPS), and tetraacetyl phytosphingosine (TAPS). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…Chronic UVB irradiation induced epidermal thickness and collagen loss (as hydroxyproline) was seen in our present study. These results closely match those of others studies which showed a reduction of collagen synthesis in mouse skin with repeated UVB exposure (Brenneisen et al 2002;Cho et al 2008). It seems likely that the protective effect of the T. chebula fruit extract on such skin photodamage caused by chronic UVB exposure may be mediated through the free radical scavenging activity and the preservation of MMPs and procollagen expressions in dermal fibroblast.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic UVB irradiation induced epidermal thickness and collagen loss (as hydroxyproline) was seen in our present study. These results closely match those of others studies which showed a reduction of collagen synthesis in mouse skin with repeated UVB exposure (Brenneisen et al 2002;Cho et al 2008). It seems likely that the protective effect of the T. chebula fruit extract on such skin photodamage caused by chronic UVB exposure may be mediated through the free radical scavenging activity and the preservation of MMPs and procollagen expressions in dermal fibroblast.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis may be partly supported by the observation that the increased fibroblast proliferation resulted in the increase in collagen content in the skin. 8) It is not known whether low molecular weight collagen stimulates the proliferation of dermal fibroblasts. In fact, this study showed that low molecular weight collagen alone failed to stimulate the proliferation of cultured human dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…8) Collagen levels gradually decrease in the dermis 9) and the three dimensional structure of collagen fibers progressively disorganizes with age. 10) These decreases may be one of the causes of skin aging.…”
Section: Discussionmentioning
confidence: 99%
“…One microgram of the total RNA was used in a 20-ml reaction volume for first-strand cDNA synthesis using a first-strand cDNA synthesis kit for RT-PCR, according to the manufacturer's instructions (MBI Fermentas, Vilnius, Lithuania). Semi-quantitative RT-PCR was performed using 1 ml of the first-strand cDNA product using the following primers for the human genes: 36B4 (cDNA for human acidic ribosomal phosphoprotein PO), which did not change with UV irradiation (Cho et al, 2008)…”
Section: Rna Analysismentioning
confidence: 99%